Организационная модель социализации различных гетерогенных групп в условиях инклюзивной среды университета - Валетов, Валентин Васильевич; Лебедев, Николай Александрович; Журлова, Ирина Владимировна; Палиева, Татьяна Владиславовна (International Dialogues on Education Journal, 2017)
Through the example of organization of a holistic inclusive atmosphere in the „Pedagogical State University Mozyrsk, named I.P. Shamyakin“ (Belarus), this article presents an organizational model for the socialization of diverse heterogeneous groups of students. These students are foreign-language speakers, or come from families with different religious backgrounds, have physical and/or mental challenges, come from families with social problems, have special capabilities in various activity fields, or belong to different youth subcultures. Based on the resulting data the authors recommend an original organizational model for the socialization of heterogeneous student groups in university contexts. This model includes external as well as internal structures. It is concerened with facilitating focused and comprehensive work with different heterogeneous groups of students. The authors suggest a catalogue of competencies for pedagogues and educational managers working in an inclusive educational space. Organizational stages of socializing activities in the various heterogeneous groups in the inclusive sphere of the university are connected to a list of priority tasks for each stage. Also explicated are the function of the structural organization of the university and the respective working platforms of the pedagogues and leading staff. The article presents and generalizes the concrete experiences of the work with heterogeneous student groups in the university.